The Impact of Population Size and Human Development Index on Open Unemployment Rates in North Sumatra (2018–2025) - Amelia; Rini Khairani Harahap; Stevani Nababan (Outline Publisher, 2026)
This research aims to evaluate the impact of Population Size and the Human Development Index (HDI) on the Open Unemployment Rate in North Sumatra Province from 2018 to 2025. Employing a quantitative methodology, this study utilizes secondary data sourced from the Central Bureau of Statistics (BPS). The analytical framework is constructed using Multiple Linear Regression, processed via SPSS software, and validated through classical assumption tests, t-tests, F-tests, and the coefficient of determination (R2).The findings reveal that, partially, Population Size exerts a negative but statistically insignificant influence on the Open Unemployment Rate, suggesting that demographic growth does not necessarily trigger unemployment if labor absorption remains stable. In contrast, the Human Development Index (HDI) demonstrates a significant positive correlation with unemployment levels, indicating that higher human capital quality may temporarily increase the unemployment rate due to more selective job-seeking behaviors among educated individuals. Simultaneously, both variables significantly influence the Open Unemployment Rate, with a high coefficient of determination confirming their collective ability to explain the majority of fluctuations in the regional labor market. These results underscore that enhancing human resource quality profoundly shapes labor market dynamics, particularly in the short run. Consequently, integrated policies that synchronize human development with industrial expansion are essential for a sustainable reduction in unemployment.